The development of a composite sustainable development indicator for a corporate retail enterprise - Rosenburg, Saul; Mabin, Marshall; Ackermann, Neil; Fortoh, Ernest (Department of Environmental and Geographical Science, 2015)
Includes bibliographical references (leaves 134-145).